Proposição de uma UEPS: contribuições para aprendizagem significativa de conceitos de mecânica - Diniz, Vagner Schillreff (2022)
In the present work, a pedagogical proposal for the teaching of Mechanics is presented, based on a Potentially Significant Teaching Unit (UEPS) developed with the aim of investigating what characteristics a UEPS should have on Mechanics concepts capable of contributing to a significant learning of students of the 1st grade of High School, which will serve as a basis for the creation of a 3D Virtual World. This research is characterized as qualitative with a focus on content analysis and is theoretically based on specific references related to Learning Theories, namely: Mediation Theory, Meaningful Learning Theory and Critical Meaningful Learning Theory. The Systematic Literature Review (RSL) is guided by four research questions, which encompass the use of Three-Dimensional Virtual Worlds (3DVM) for Physics Teaching from the perspective of the learning topics covered, their forms of application and evaluation methods of the teaching and learning. The RSL was developed through the search and analysis of articles, theses and dissertations published in Academic-Scientific Periodicals and in the Brazilian Digital Library of Theses and Dissertations (BDTD) that deal with the construction and use of MV3D in the educational field, with a focus on teaching Physical. The RSL phases: Definition, Execution and Analysis, provided an overview of research on the subject in the area of teaching physics/science education, with an indication of the main characteristics of the studies, which are contents and platforms used in the development and use of the MV3D, as well as its contributions and potentialities in the teaching and learning process of Physics. Despite the exploratory nature of this research, its main objective is to characterize the productions in the area, related to the theme already highlighted. In addition, our didactic proposition can be summarized by presenting the following characteristics: first, the importance of searching for preconceptions acquired in physics by students in the 1st year of high school; second, according to the planning of practical experimental activities by the teacher for the construction of fundamental concepts and the Laws of Physics; third, the importance of the teacher's guidance in the students' conclusions when developing practical activities related to the physical concepts of force, movement, Newton's laws, gravitational attraction, in order to explain the dynamics and functioning of the playground toys (swing, seesaw, slide and spinner). In this sense, the UEPS is structured from eight steps described by Moreira (2016), aimed at real didactic activities so that the student can learn “the physics of the square”.